How sanctions work Iran and the impact of economic warfare - Bajoghli, Narges 1982-; Naṣr, Walī Riḍā 1960-; Salehi-Isfahani, Djavad (Stanford University Press, 2024)
"Sanctions have enormous consequences. Especially when imposed by a country with the economic influence of the United States, sanctions induce clear shockwaves in both the economy and political culture of the targeted state, and in the everyday lives of citizens. But do economic sanctions induce the behavioral changes intended? Do sanctions work in the way they should ? To answer these questions, the authors of How Sanctions Work highlight Iran, the most sanctioned country in the world. Comprehensive sanctions are meant to induce uprisings or pressures to change the behavior of the ruling establishment, or to weaken its hold on power. But, after four decades, the case of Iran shows the opposite to be true: sanctions strengthened the Iranian state, impoverished its population, increased state repression, and escalated Iran's military posture toward the U.S. and its allies in the region. Instead of offering an 'alternative to war,' sanctions have become a cause of war. Consequently, this book reveals how necessary it is to understand how sanctions really work."
Includes bibliographical references and index
Keywords: Sanktion / (DE-627)091387698 / (DE-2867)18064-5; Wirkungsanalyse / (DE-627)09140116X / (DE-2867)10991-6; Iran / (DE-627)091369126 / (DE-2867)17622-2; USA / (DE-627)091396867 / (DE-2867)17829-1; Economic sanctions / Iran; Economic sanctions, American / Iran; Iran / Economic conditions; Iran / Politics and government; United States / Foreign relations / Iran; Iran / Foreign relations / United States